THE SYSTEM OF SIGN COMMUNICATION BETWEEN A DENTIST AND A PATIENT (Uzbekistan Open Conference, 2025)
Modern dental practice requires not only technical excellence but also effective communication between the dentist and the patient. However, during dental procedures, the patient is unable to speak, which complicates feedback and increases anxiety levels. This paper proposes a system of gesture-based communication consisting of five to six simple and intuitive gestures that allow the patient to inform the dentist about their condition - pain, desire to pause, rinse the mouth, etc. For convenience, visual cues depicting these gestures are placed on the ceiling of the dental office - in the area where the patient’s gaze is most often directed. A brief introduction to the gestures is provided before the procedure. The implementation of such a system requires no technical costs but significantly improves comfort, trust, and safety during treatment. The proposed concept may become part of the standards of ethical and patient-centered dental care.